A digital twin for monitoring land use/cover and coastal change in Tobago - D. Ramsewak; A. Jagassar; B. Edwards; A. Potts (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Digital twin technology presents a transformative opportunity for monitoring land use and coastal changes on small islands. These comprehensive virtual models help to mirror physical environments, thereby offering real-time data integration, simulation, and predictive analytics. The island of Tobago, in the southeastern Caribbean Sea, has diverse landscapes and coastal regions ranging from tropical forests and mangrove ecosystems to thriving coral reefs and seagrass beds. In this study, high resolution digital elevation data was used to model the topography of the island. A land use and land cover information layer, generated from high resolution satellite imagery was then draped over the elevation model to illustrate the variation across the small, mountainous tropical island. An updated high-resolution satellite image base layer of the nearshore marine environment was also integrated into the model along with polygons demarcating the distribution and extent of key coastal ecosystems such as coral reefs. The key to digital twins lies in their ability to provide accurate and up-to-date spatial data and environmental insights. This virtual replica allows for detailed analysis of changing land use and habitat loss, helping stakeholders to make informed decisions. By integrating data from various sources such as satellite imagery, geographic information systems (GIS), and in-situ measurements the digital twin facilitates comprehensive monitoring and forecasting of land and coastal changes. For Tobago, this digital model can enhance understanding and management of its dynamic coastal and land use environments, which are increasingly threatened by climate change, urbanization, and natural disasters.